A Differential Innate Immune Response in Active and Chronic Stages of Bovine Infectious Digital Dermatitis - Watts, Kaitlyn M.; Fodor, Cristina; Beninger, Caroline; Lahiri, Priyoshi; Arrazuria, Rakel; De Buck, Jeroen; Knight, Cameron G.; Orsel, Karin; Barkema, Herman W.; Cobo, Eduardo R. (Frontiers in Microbiology, 2018)
Digital dermatitis (DD) commonly associated with Treponema spp. infection is a prevalent infectious bovine foot disease characterized by ulcerative and necrotic lesions. Lesions associated with DD are often classified using the M-stage scoring system, with M0 indicating healthy heel skin and M4 indicating chronic lesions. Current treatments utilizing antimicrobials or chemical footbaths are often ineffective and rarely cure DD lesions. Understanding the function of the innate immune response in the pathogenesis of DD will help to identify novel therapeutic approaches. In this study, the expression of the local innate host defense peptides cathelicidins and β-defensins was investigated in cows with DD and associated with the presence of treponemes and inflammatory reactions. Samples from active ulcerative DD lesions (M2) had considerable epidermal neutrophilic infiltration and increased gene expression of β-defensin tracheal antimicrobial peptides compared to control skin. Samples from acute lesions also had elevated local Cxcl-8 and TLR4 gene expression and abundant treponemes as identified by direct visualization, immunohistochemistry, and culture. Conversely, the anti-inflammatory peptide IL-10 was elevated in skin from chronic (M4) lesions, whereas bovine cathelicidin myeloid antimicrobial peptide 28 (Bmap-28) was increased in skin from oxytetracycline-treated M2 lesions. Experiments using cultured human keratinocytes challenged with Treponema spp. isolated from clinical cases of bovine DD showed that structural products from treponemes are able to initiate the innate immune response, in part through TLR2 signaling. These findings indicate that neutrophil influx, Cxcl-8, and β-defensin are key markers of active DD. Cathelicidins and IL-10 seem important in response to treatment or during the chronic proliferative stages of the disease.